Donor surfactant protein A2 polymorphism and lung transplant survival. Issue 3 (5th March 2020) - D'Ovidio, Frank; Floros, Joanna; Aramini, Beatrice; Lederer, David; DiAngelo, Susan L.; Arcasoy, Selim; Sonett, Joshua R.; Robbins, Hillary; Shah, Lory; Costa, Joseph; Urso, Andreacarola
Purpose: Gene polymorphisms of surfactant proteins, key players in lung innate immunity, have been associated with various lung diseases. The aim of this study was to investigate the potential association between variations within the surfactant protein (SP)-A gene of the donor lung allograft and recipient post-transplant outcome. Methods: Lung-transplant patients (n=192) were prospectively followed-up with pulmonary function tests, bronchoscopies with bronchoalveolar lavage and biopsies. Donor lungs were assayed for SP-A1 (6A n ) and SP-A2 (1A n ) gene polymorphism using the pyrosequencing method. Unadjusted and adjusted stratified Cox survival models are reported. Results: SP-A1 and SP-A2 genotype frequency and lung transplant recipient and donor characteristics as well as cause of death are noted. Recipients were grouped per donor SP-A2 variants. Individuals that received lungs from donors with the SP-A2 1A 0 (n=102) versus 1A 1 variant (n=68) or SP-A2 genotype 1A 0 1A 0 (n=54) versus 1A 0 A 1 (n=38) had greater survival at 1 year (log-rank p<0.025). No significant association was noted for SP-A1 variants. Stratified adjusted survival models for 1-year survival and diagnosis showed a reduced survival for 1A 1 variant and the 1A 0 1A 1 genotype. Furthermore, when survival was conditional on 1-year survival no significance was observed, indicating that the survival difference was due to the first year's outcome associated with the 1A 1 variant. Conclusion: Donor lung SP-A gene polymorphisms are associated with post-transplant clinical outcome. Lungs from donors with the SP-A2 variant 1A 1 had a reduced survival at 1 year. The observed donor genetic differences, via innate immunity relate to the post-transplant clinical outcome. Donor genetic polymorphisms of the lung-specific innate defence systems determine post-lung transplant recipient outcome http://bit.ly/2QNpX7Q